Advances in genetics. (Academic Press, 2022)
Advances in Genetics, Volume 109 in this ongoing series, highlights new advances in the field, with this new volume presenting interesting chapters written by an international board of authors. Chapters in this new release include Epigenetic regulation of angiogenesis in tumor progression, RecBCD and Chi hotspots as determinants of self vs. non-self: A re-evaluation, Horizontal gene transfer to plants from Agrobacterium and related bacterial species, and more.